Snowflake : build and architect data pipelines using AWS. (Packt Publishing, 2022)
Be a part of a comprehensive course on AWS and Snowflake integration. Leverage your learning with a power-packed and well-structured course with an adequate pace. About This Video Learn from an easy-to-understand and step-by-step course, divided into 85+ videos along with detailed resource files Integrate real-time streaming data and data orchestration with Airflow and Snowflake Highly practical explanations and lab exercises to help you grasp the most out of the course In Detail Snowflake is the next big thing, and it is becoming a full-blown data ecosystem. With the level of scalability and efficiency in handling massive volumes of data and also with several new concepts in it, this is the right time to wrap your head around Snowflake and have it in your toolkit. This course not only covers the core features of Snowflake but also teaches you how to deploy Python/PySpark jobs in AWS Glue and Airflow that communicate with Snowflake, which is one of the most important aspects of building pipelines. In this course, you will look at Snowflake, and then the most crucial aspects of Snowflake in an efficient manner. You will be writing Python/Spark Jobs in AWS Glue Jobs for data transformation and seeing real-time streaming using Kafka and Snowflake. You will be interacting with external functions and use cases, and finally, see the security features in Snowflake. By the end of this course, you will have learned about Snowflake and learned how to build and architect data pipelines using AWS. You need to have an active AWS account in order to perform the sections related to Python and PySpark. For the rest of the course, a free trial Snowflake account should suffice. Audience This course is ideal for Software engineers, aspiring data engineers or data analysts, and data scientists who want to excel in their careers in the IT domain. Apart from them, this course is also good for programmers and database administrators with experience in writing SQL queries. A prior programming experience in SQL or at least some prior knowledge in writing queries and Python is a must. You should have a basic experience or understanding of cloud services such as AWS is important along with an active AWS account.